The Influence of Entrepreneurship Education, Use of Social Media, Availability of Information, Against Entrepreneurial Interests of FEB Unhar Students With Self Efficacy As Moderating Variable - Aulia, Meidy; Badawi, Ahmad (Cattleya Darmaya Fortuna, 2023)
This study aims to determine whether entrepreneurship education, the use of social media and the availability of information affect the interest in entrepreneurship, to determine whether self-efficacy affects the interest in entrepreneurship, to determine whether self-efficacy is able to moderate entrepreneurial education to the interest in entrepreneurship, to determine whether self-efficacy is able to moderate the use of social media on the interest in entrepreneurship and to find out whether self-efficacy is able to moderate the availability of information on the interest in entrepreneurship. The total population in this study amounted to 374 students of the Faculty of Business Economics, Harapan University Medan, and the sample taken was 30% from 374 to 112 people. The analysis technique used is multiple linear regression and MRA.The results showed that entrepreneurship education, use of social media and availability of information had a significant effect on interest in entrepreneurship, self-efficacy had an effect on interest in entrepreneurship, self-efficacy moderated the effect of entrepreneurship education on interest in entrepreneurship, self -efficacy did not moderate the effect of using social media on interest in entrepreneurship, and self-efficacy did not moderate the effect of information availability on entrepreneurial interest in students of the Faculty of Business Economics, Universitas Harapan